Penerapan Lafazh Ditinjau dari Segi Dalalahnya - Kartini Kartini (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
This study is motivated by the problem of a jurist (faqih), to know how to extract the law from the texts. For that purpose, the science of Ushul al-Fiqh has established its methodology. This research, using the method of library research (library research), namely research with quotations on the books usul al-fiqh as primary sources and books that exist with this research as a source sekunder. Dalam processing data obtained from the library, the authors use qualitative methods, with inductive and deductive forms of analysis. The pronunciation in full of nash comprehension is an indication of the criticism of the texts themselves. Being mafhum is understanding or understanding or not placed in place of speech, from the understanding of the speech. The mafhum is divided into two parts: mafhum muwafaqah and mafhum mukhalafah. Mafhum muwafaqah is the guidance of the pronunciation of nash or the determination of a law for the case that exist between the two there is a suitability because there is an illat equation. While mukhummukhalafah is a law for those who are not criticized by the nash opposed by the precious. Or in other words, something that nash does not criticize with that in its legal determination. Mafhum muwafaqah consists of two, namely lahn al-khitab and fahwa al-khitab. While mukhum mukhalafah consists of mafhum al-shifah, mafhum al-ghayah, mafhum al-syarth, mafhum al-'adad, and mafhum al-laqab. Mantuq is the language of